Egy világméretű sportesemény, a 2017 Vizes Világbajnokság néhány társadalmi aspektusa a jövő managereinek szemszögéből a felkészülési időszakban - Bene, Ágnes; Móré, Mariann (International Journal of Engineering and Management Sciences, 2017)
Hungary hosts the 2017 FINA World Championships and Master’s Championships, one of the world’s largest sport event. Besides exploring the influential factors behind the potential effectivity, this study aims to identify social effects related to the event. Students in higher education today are the next generation of managers and company owners, therefore their attitudes and opinions will be determinative in terms of the decision-making. The empirical research took place in the University of Debrecen, the most populouses University of Hungary, 6 month before the official opening ceremony of the Championships.